1994
DOI: 10.1111/j.1365-3024.1994.tb00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Human monocytes cultured with and without interferon‐gamma inhibit Plasmodium falciparum parasite growth in vitro via secretion of reactive nitrogen intermediates

Abstract: Adherent cells from human peripheral blood were studied for their interaction with asexual blood forms of Plasmodium falciparum in vitro. Freshly isolated monocytes only showed weak anti-parasitic effects. However, an enhancement of this anti-parasitic activity was apparent when monocytes were allowed to mature in vitro. Monocytes activated with IFN-gamma for two or three days had an enhanced anti-parasitic effect. In contrast, the inhibition mediated by cells incubated for five days was the same with or witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 20 publications
1
41
0
1
Order By: Relevance
“…Among the various host cytokines, IFN-␥ has been identified as an important M activator during plasmodial infection (43) and, thus, as central in the regulation of NO synthesis (8). In addition to host products, purified malarial GPI was shown to induce NO release in murine M and to synergize with IFN-␥ in regulating NO production (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various host cytokines, IFN-␥ has been identified as an important M activator during plasmodial infection (43) and, thus, as central in the regulation of NO synthesis (8). In addition to host products, purified malarial GPI was shown to induce NO release in murine M and to synergize with IFN-␥ in regulating NO production (13).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies regarding its role during malaria have revealed that NO can exert both beneficial and detrimental effects on the host, depending on, among other things, the timing and amounts of its production and the biological milieu in which it is released (7). As a host defender, NO has been shown to mediate in vitro killing of both hepatic and blood forms of malaria parasites in response to IFN-␥ (8,9). These results have been further supported in vivo by demonstrating that protection against parasite challenge requires IFN-␥ and occurs via a NO-dependent mechanism (10).…”
mentioning
confidence: 99%
“…2 Nitric oxide production/MNC NOS2 expression was higher in those asymptomatic children with parasitemia found on thick film examination, suggesting that NO production in these children may in part be due to the known ability of parasites to induce macrophage NOS activity. 3,4 However, the majority of the asymptomatic children with constitutive expression of NOS2 were thick film negative, raising the possibility that NOS2 expression was due to parasitemia below the detection limits of microscopy, subclinical infection with other pathogens, or age-related physiologic NOS2 expression in childhood.…”
mentioning
confidence: 99%
“…Studies have shown that severe cases of malaria are accompanied by increased iNOS activity and the subsequent production of NO (Bryk et al, 2000). Increased levels of NO were found to be beneficial, as NO was shown to kill parasites (Gyan et al, 1994;Rockett et al, 1991). The LPS are believed to be potent inducers of macrophage ROI and RNI against a variety of intracellular and extracellular pathogens and to be potent stimulators of NOS isoforms (Nahrevanian, 2006).…”
Section: Discussionmentioning
confidence: 99%